Produção de β-1,3-glunacase por Rhodotorula oryzicola isolada do semiárido baiano - Pereira, Manuela Oliveira (2022)
Enzymes are versatile catalysts present in animal, plant and microorganism cells; they have several properties that make them attractive as catalysts in various bioprocesses. β-glucanases consist of a set of enzymes that act synergistically to degrade glucan, its potential is explored in the beverage industry to improve organoleptic characteristics of wines, in feed supplementation, in biological control and in the manufacture of detergents. The objective of this work was to evaluate and characterize the β-1,3-glucanase activity by the yeast Rhodotorula oryzicola cultivated in liquid medium. Response surface analysis was used to determine the most suitable pH and temperature parameters for enzymatic activity. Thermostability was studied at temperatures from 50 oC to 70 oC, in times ranging from 0 to 50 min. The influence of NaCl at concentrations from 0.2 to 1 M was evaluated. A centroid simplex mixture design was used in the study of enzyme stabilization by a mixture of preservatives composed of sodium chloride (SC), sodium benzoate (SB) and monosodium phosphate (MSP). The optimum conditions of enzymatic activity were obtained at 50oC and pH 8.0 with activity of 0.9601 μmol/min. After 30 minutes of incubation in 50, 60 oC and 70 oC enzymatic activity remained at 100%, 94.6% and 62.39%, respectively. The presence of NaCl increased enzymatic activity in all concentrations studied. In the study of preservatives, according to the response surface of the cubic model, the best result was obtained in the proportion of 20% sodium chloride, 70% sodium benzoate and 10% monosodium phosphate. The results show that yeast is capable of producing the enzyme β-1,3-glucanase and stabilizers have shown promise to maintain enzymatic stability in preparations.